Go-kart mechanical linkage steering system - Abdul Razak, Auni Azira (2025)
The revolution of go-kart steering system shown from their beginnings, go-kart mechanical linkage steering system used till now. This go-kart mechanical linkage steering system have improved into more advanced design and technology. The rack and pinion system and hydraulic system has been used in achieving optimal performance and control for go-kart mechanical system. The key components for build a go-kart steering system is the steering column, tie rods, steering knuckles, steering wheels, linkage or system such as rack and pinion. All of the components will work on their functions to contribute the system function smoothly. These components will be able to do a task given by the driver by receiving input and precise wheel movements will be out as an output. The study aims to explore the performance characteristic and applications of the steering system of the go-kart. It will investigate factors such as the movement, the direction, the material used, and the pressure that effect the mechanical linkage steering system. Furthermore, the research will identify the suitable components to be used in steering system and the effectiveness of type of system used. The findings form this study will contribute to improve the understanding in steering system of go-kart.